Land, politics, and memory in five Nija'ib' K'iche' títulos: "The title and proof of our ancestors" - Matsumoto, Mallory, author; University Press of Colorado, publisher (Colorado State University. Libraries, 2017)
Five highland Maya títulos composed in the sixteenth century by the Nija'ib K'iche' of Guatemala. Each manuscript provides a copy of the original, a transcription of the sixteenth-century modified Latin script, a morphologic analysis, a line-by-line English translation preserving the original syntax, and English prose versions.--Provided by publisher.
Títulos in colonial Mesoamerica and their highland Guatemalan context -- The Nija'ib' títulos: history, contents, and current state of research -- Rewriting the títulos: philological and linguistic methodology for preparing the publication -- Scribal practice in the Nija'ib' títulos -- Appendices: Orthographic correspondence tables for the Nija'ib' títulos -- The Nija'ib' títulos in Garrett-Gates Mesoamerican Manuscript No. 101: Utitulo rajawarem ajaw Don Francisco Iskin Nija'ib' (folios 1r/8v). Utitulo ulew rech ajaw Don Francisco Iskin Nija'ib' (folios 9r/9v, 10v). Inpormacion chi rij título (folio 10r). Titulo Iskin rech Quetzaltenango, Momostenango (folio 11r). Título de Quetzaltenango y Momostenango y conquistas de nuestros.
Keywords: Quiché Indians -- Guatemala -- Texts; Quiché language -- Transcription; Oral history -- Guatemala; Indian literature -- Guatemala